Y(3940) as a mixed charmonium-molecule state - Albuquerque, R. M. [UNESP]; Dias, J. M.; Nielsen, M.; Zanetti, C. M. (Amer Physical Soc, 2014)
Using the QCD sum rules approach, we study the mass and the decay widths of the Y(3940) state, assuming that it can be described by a mixed charmonium-molecule scalar state, i.e., a mixture between chi(c0) charmonium and D*(D) over bar* molecule. Using a current with J(PC) = 0(++), we estimate for the mixing angle, theta = (76.0+/-5.0)degrees, resulting in a mass value of M-Y = (3.95 +/- 0.11) GeV, which is in reasonable agreement with the experimental mass of the Y(3940) state. For the decay width, we evaluate the channels Y -> J/psi omega and Y -> gamma gamma. We find the values Gamma(Y -> J/psi omega) approximate to (1.7 +/- 0.6) MeV and Gamma(Y ->gamma gamma) approximate to (1.6 +/- 1.3) KeV, respectively. We also study the decay process of this state into channels containing D (D) over bar mesons in the final state. The result for the order of magnitude of the product Gamma(Y ->gamma gamma) X Gamma(Y -> J/psi omega) similar to O (10(3)) KeV(2) is also in reasonable agreement with the experimental data. We thus conclude that the present description of the Y(3940) as a mixed charmonium-molecule state is a possible scenario to explain the structure of such a state.